2009
DOI: 10.1093/molehr/gap103
|View full text |Cite
|
Sign up to set email alerts
|

The differential transcriptome and ontology profiles of floating and cumulus granulosa cells in stimulated human antral follicles

Abstract: Communication between various ovarian cell types is a prerequisite for folliculogenesis and ovulation. In antral follicles granulosa cells divide into two distinct populations of mural and cumulus granulosa cells (CGC), enveloping the antrum and surrounding the oocyte, respectively. Both cell types, with the mural compartment in excess, contribute to the floating granulosa cell (FGC) population in the follicular fluid. The aim of this study was to compare the transcriptomes of FGC and CGC in stimulated antral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 74 publications
13
50
0
Order By: Relevance
“…Cytokines are important in the regulation of ovarian function and oocyte quality [25]. On the other hand interleukins IL18 and IL1 β were reported to be present in floating granulosa cells of human preovulatory follicles [26]. CC median group may be characterized by an overexpression of gene members of the “insulin-signaling pathway”, such as IGFBP3 and IGFBP5 whereas INSR was overexpressed in both the CC median and CC older groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines are important in the regulation of ovarian function and oocyte quality [25]. On the other hand interleukins IL18 and IL1 β were reported to be present in floating granulosa cells of human preovulatory follicles [26]. CC median group may be characterized by an overexpression of gene members of the “insulin-signaling pathway”, such as IGFBP3 and IGFBP5 whereas INSR was overexpressed in both the CC median and CC older groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be associated with pathology and induced by microenvironmental factors like hypoxia. In this context, the follicular cells synthesize several angiogenic factors [26, 35, 36], among which the vascular endothelial growth factor C ( VEGFC ) and angiopoietin-like 4 ( ANGPTL4 ), which are induced in response to hypoxic stimuli [3739]. So, the overexpression of angiogenic factors and hypoxia-inducible protein 2 ( HIG2 ) in the CC older group could be caused by insufficiency of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were further supported by subsequent studies that measured global gene expression of cumulus cells, which was concluded to be a non-invasive test for oocyte/embryo quality [2,3,15,41]. Granulosa and cumulus cell gene expression profiling has also been used to compare the effects of recombinant FSH vs. human menopausal gonadotrophin (hMG) [6,14], floating vs. cumulus granulosa cells [22], cumulus cells from lean vs. overweight-obese PCOS patients [21], and ovarian reserve status in young women with diminished ovarian reserve [39].…”
Section: Introductionmentioning
confidence: 87%
“…When comparing CC to MGC, more than 1500 RNAs varied by ≥2-fold between the two cell types. A third study examined MGC and CC samples from mature oocytes (Burnik et al 2015b) and conducted a meta-analysis with the data generated from the previous two studies ( Koks et al 2010, Grondahl et al 2012. When genes with log 2 fold-change ≥2 were evaluated collectively, 3156 genes were differentially expressed.…”
Section: Follicular Cumulus and Mural Granulosa Cell Differencesmentioning
confidence: 99%